Stats NZ Integrated Data Population Explorer Prototype – using data visualisation to increase usability of large scale, complex and messy data - Lefebre, Aaron; Ashby, Lucy; McDowell, Anna; Blackburn, Andrea (International Journal of Population Data Science, 2018)
Introduction Stats NZ works with a range of organisations to provide the world-leading Integrated Data Infrastructure (IDI) to help improve New Zealanders’ lives. IDI is a critical tool in our government’s efforts to reduce poverty, improve health, and provide a growing, inclusive economy. It enables evidence-based insights, and measurement of government services. Objectives and Approach Users currently need a large degree of technical capability to access and use the IDI. Our Population Explorer Prototype is an integrated data digital product designed to increase the use and improve the usability of the IDI by reducing barriers for current researchers and new customer groups. Results The Population Explorer Prototype makes it easier and more efficient for new and existing users to gain insights from data by shifting from having to repeatedly carry out complex coding to get information in tables, to being able to “point and click” to see information in a range of visual, easy-to-understand formats. There is wide excitement in the data community about this product’s potential and implementing user feedback has been a key part of improving the product. Conclusion/Implications We have only scratched the surface of what is possible with integrated data, and the Population Explorer Prototype is the next frontier. The Population Explorer Prototype will unleash the power of data to change peoples’ lives to a wider range of researchers, while protecting privacy and security.